FOAM DRESSING ON WOUND HEALING PROSES IN POST FRACTURE OPERATION PATIENTS - oktaffrastya widhamurti septafani; Septian Dwi Nugroho (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Modern wound dressing is a technique of wound care that focuses on moist principles so that the use of wound dressing plays an important role in accelerating the wound healing process. This study aims to determine the Effect of Modern Wound Care with Foam Dressing on the Wound Healing Process of Post Patient's Femur Fracture Surgery. The study used a pre-experiment one group pretest posttest design. The sampling used was accident sampling. The independent variable of the study was modern wound care with foam dressing, and the dependent variable of the study was the wound healing process, assessed by Bates-Jensen Wound Assessment tools. The results of the study before the intervention, the mean Bates-Jensen Wound Assessment score was 23.50 with a standard deviation of 1.080, a minimum value of 23.00 and a maximum value of 26.00. The results of the study after the intervention, the mean score was 15.50 with a standard deviation of 0.850, a minimum value of 15.50 and a maximum value of 17.00. Post operative wound care with foam dressings is expected to be applied and routinely carried out according to the wound care schedule of postoperative patients in order to improve the quality of health services.